(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
In the current conditions of growing competition both between individual countries and individual regions for investment resources, the issues of competitiveness of territories are becoming increasingly important. Obviously, other things being equal institutional conditions, the region that is able to implement marketing tools into its investment policy will have a greater investment attractiveness, that is, to demonstrate its advantages to potential investors as efficiently as possible [1, p. 145]. Using the example of the administrative region of Flanders (Kingdom of Belgium), the article describes a successful experience in the use of investment marketing of the territory.